2009
DOI: 10.4049/jimmunol.0901654
|View full text |Cite
|
Sign up to set email alerts
|

Cytohesin-1 Regulates the Arf6-Phospholipase D Signaling Axis in Human Neutrophils: Impact on Superoxide Anion Production and Secretion

Abstract: Polymorphonuclear neutrophil (PMN) stimulation with fMLP stimulates small G proteins such as ADP-ribosylation factors (Arfs) Arf1 and Arf6, leading to phospholipase D (PLD) activation and functions such as degranulation and the oxidative burst. However, the molecular links between fMLF receptors and PLD remain unclear. PMNs express cytohesin-1, an Arf-guanine exchange factor that activates Arfs, and its expression is strongly induced during the acquisition of the neutrophilic phenotype by neutrophil-like cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 81 publications
3
47
0
Order By: Relevance
“…PI3Ks and Rho, Rap, and Arf family small GTPases are involved in regulating the phagocyte oxidase. 6,9,30 We found no difference in ROS production by neutrophils from tamoxifen-or mock-induced Arap3 fl/fl ERT2Cre ϩ mice or controls after stimulation with the soluble agonist fMLF ( Figure 2A-B and supplemental Figure 1A for controls), nor with the nonphysiologic, soluble stimulus phorbol 12-myristate 13-acetate (data not shown). This indicated that the machinery required for ROS production was intact in neutrophils lacking ARAP3.…”
Section: Arap3 Regulates Adhesion-dependent Formation Of Rosmentioning
confidence: 85%
See 1 more Smart Citation
“…PI3Ks and Rho, Rap, and Arf family small GTPases are involved in regulating the phagocyte oxidase. 6,9,30 We found no difference in ROS production by neutrophils from tamoxifen-or mock-induced Arap3 fl/fl ERT2Cre ϩ mice or controls after stimulation with the soluble agonist fMLF ( Figure 2A-B and supplemental Figure 1A for controls), nor with the nonphysiologic, soluble stimulus phorbol 12-myristate 13-acetate (data not shown). This indicated that the machinery required for ROS production was intact in neutrophils lacking ARAP3.…”
Section: Arap3 Regulates Adhesion-dependent Formation Of Rosmentioning
confidence: 85%
“…Rho family small GTPases are involved in regulating the neutrophil NADPH oxidase and chemotaxis, 6,7 whereas Arf family members regulate phagocytosis, ROS production, and chemotaxis. 8,9 ARAP3 was identified from porcine neutrophils in a screen for PtdIns(3,4,5)P 3 -binding proteins. In vitro, ARAP3 is a PtdIns(3,4,5)P 3 -dependent Arf6 GAP and a Rap-activated RhoA GAP.…”
Section: Introductionmentioning
confidence: 99%
“…[14,15]. An elegantly described study in human neutrophils, demonstrated the regulation of Arf6-PLD signaling in superoxide production by cytohesin-1, another family member of ARNO [23]. As a logical connection to all the evidences, we tested the effect of secinH3 on the translocation of p47 phox to the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the context of our current investigation, activation of Nox2 has been linked to Arf6-PLD signaling axis in polymorphonuclear leukocytes [23]. Therefore, we next determined if glucose-induced phosphorylation and membrane association of p47 phox , a member of the cytosolic core of Nox2 [24] are regulated by a signaling step involving activation of Arf6 by ARNO.…”
Section: Inhibition Of Arno-arf6 Signaling Pathway Attenuates Glucosementioning
confidence: 99%
“…ARF1 activates PLD1 in vitro by increasing the catalytic constant without changes in the K m value [80]. The replacement of GDP by GTP in ARF6 is important for activation of PLD [114], and this explains the stimulatory effect of guanine nucleotide exchange factors on the activity of PLD1 in vivo [115,116]. The N-terminus of PLD2 (amino acids 1-308) is essential for modification of this enzyme activity through ARF.…”
Section: +mentioning
confidence: 99%